2009
DOI: 10.1159/000189704
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of Early Childhood Caries in Australia

Abstract: The aim of this case-control study of 617 children was to investigate early childhood caries (ECC) risk indicators in a non-fluoridated region in Australia. ECC cases were recruited from childcare facilities, public hospitals and private specialist clinics to source children from different socioeconomic backgrounds. Non-ECC controls were recruited from the same childcare facilities. A multinomial logistic modelling approach was used for statistical analysis. The results showed that a large percentage of childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
176
4
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(201 citation statements)
references
References 69 publications
(40 reference statements)
8
176
4
13
Order By: Relevance
“…Parental stress has been reported as a potential risk factor for caries in preschool children 14,17,18 , and parents' and caregivers' cognitive characteristics have also been associated with caries in this group 19 . Other psychosocial factors, like alcohol abuse in the family and maternal psychiatric disorders have been associated with this condition 14,15,16 . Quiñonez et al 18 also observed that severe early caries was associated with psychosocial alterations, as in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental stress has been reported as a potential risk factor for caries in preschool children 14,17,18 , and parents' and caregivers' cognitive characteristics have also been associated with caries in this group 19 . Other psychosocial factors, like alcohol abuse in the family and maternal psychiatric disorders have been associated with this condition 14,15,16 . Quiñonez et al 18 also observed that severe early caries was associated with psychosocial alterations, as in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Living conditions and psychosocial aspects of the family context can also contribute to the development of caries, including mental disorders 14,15,16,17,18 and cognitive factors 19 . Multivariate analyses and longitudinal studies on this topic are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported the use of bottle feeding and breastfeeding as ECC risk factors, whereas the results of other studies found no effect by the 2 risk factors or differences between them (22)(23)(24)(25)(26). The length of breast and bottle feeding may play a role to caries development.…”
Section: Etiologymentioning
confidence: 99%
“…7,8 EÇÇ GÖRÜLME SIKLIĞI VE DAĞILIMI Diş çürüğünü önlemeye yönelik koruyucu uygulamalara rağmen EÇÇ, tüm dünyayı ilgilendiren bir sağlık sorunu olmaya devam etmektedir. 9 Yaş aralığı 2-4 yıl olan çocuklarda EÇÇ prevalansının 1988-1994 yılları arasında %18,5 olduğu, 1999-2004 yılları arasında ise bu prevalansın %23,7'ye yükseldiği rapor edilmektedir. Bu yaş grubunda belirlenmiş hedef 2010'lu yıllarda %11 olarak açık-lanmaktadır.…”
unclassified